Sombreamento arbóreo em superfícies pavimentadas de área urbana tropical - Miranda, Soneize Auxiliadora de (2018)
In regions of tropical climate, tree shading on paved surfaces exerts a direct influence on the thermal ambiance of open spaces. However, the potential of the shading strategy is associated to factors of urban morphology, atmospheric variables and tree cover factors, such as the seasonal variation of the arboreal canopy and the attenuation of solar radiation. In this context, the general objective of the study was to analyze the relationships between spatial factors, tree cover and shading in paved parking lots, through the integration of research and exploratory research. The study was developed through the microclimatic evaluation in eight samples of parking lots of two typologies for afforestation; soil cover and tree cover characterization (TC), analysis of homogeneous groups and the correlation between soil cover attributes. After evaluation of the results, three-dimensional simulations of tree shading were developed in surface parking lots for the city of Cuiabá-MT. The evaluation of the results indicated that the seasonal effect of TC was significant, among the evaluated parking lots the seasonal variation was -2.6% to -25% in the dry period. The spatial variation of the variables verified was significant among the parking lots, ratified by the homogeneous groups, with greater microclimatic similarity between the parking lots with greater distribution of the trees and between the parking lots with lower tree cover, however there was no seasonal variation of the homogeneous groups. The observed results indicate that the spatial distribution of the TC and the immediate surroundings provided a greater impact on the microclimatic variables, in relation to the seasonal variation in the evaluated parking lots. In the evaluation of the simulated scenarios, it was observed a smaller impact of spatial factors, geographic orientation and typology of the waves, on the tree shade index (TSI) in the parking lots; however the spatial factors were significant regarding the TSI on the areas of the spaces for vehicles. With the results of this research, we hope to contribute to the insertion of better strategies in the planning and management of the trees in parking lots, aiming at a better urban environmental quality that allows collaborating for the mobility and the comfort of the pedestrians in cities of tropical climate.